Evaluative Observation in a Concealed Information Test - Ambach, Wolfgang; Assmann, Birthe; Wielandt, Blanda; Vaitl, Dieter (Frontiers in Psychiatry, 2019)
The Concealed Information Test (CIT) is a valid method to detect hidden knowledge by means of psychophysiological measures. Concealing information is always a social behavior; yet, the role of social aspects has barely been investigated in recent CIT research favoring standardized, computer-based experiments. Evaluative observation is known to influence social behavior as well as physiological measures; examining the impact of evaluative observation on physiological responding in a CIT is the aim of this study. Sixty-three students completed a mock-crime and then underwent a CIT. In a between-subjects manipulation, half of the participants were observed through a camera and were faced with the real-time video of the experimenter watching them while completing the CIT. The other half completed the CIT without observation and video. Electrodermal activity, respiration line length, phasic heart rate, and finger pulse waveform length were registered. A specific questionnaire captured the individual fear of negative evaluation. Typical differential CIT responses occurred in both groups and with each measure. Contrary to expectations, differential CIT responses did not differ between groups. No modulatory influence of the fear questionnaire score on physiological responding was found. A ceiling effect, involving high attention and high motivation to avoid detection as well as high arousal in both groups due to the CIT procedure per se is discussed as explanation for these results, while the independence of the orienting reflex of social and motivational influence appears less likely in the light of previous literature.